Slope control on the frequency distribution of shallow landslides and associated soil properties, North Island, New Zealand - De Rose, Ronald C. (Earth surface processes and landforms, 2013)
ABSTRACT The extrapolation of results from field trials to larger areas of land for purposes of regional impact assessment is an important issue in geomorphology, particularly for landform properties that show high stochastic variability in space and time, such as shallow landslide erosion. It is shown in this study, that by identifying the main driver for spatial variability in shallow landslide erosion at field scales, namely slope angle, it is possible to develop a set of generic functions for assessing the impact of landslides on selected soil properties at larger spatial scales and over longer time periods. Research was conducted within an area of pastoral soft‐rock Tertiary hill country in the North Island of New Zealand that is subject to infrequent high intensity rainfall events, producing numerous landslides, most of which are smaller than several hundred square metres in size and remove soil to shallow depths. All landslides were mapped within a 0·6 km2 area and registered to a high resolution (2 m) slope map to show that few landslides occur on slopes < 20° and 95% were on slopes > 24°. The areal density of landslides from all historical events showed an approximately linear increase with slope above 24°. Integrating landslide densities with soil recovery data demonstrates that the average value of a soil property fluctuates in a ‘saw‐tooth’ fashion through time with the overall shape of the curve controlled by the frequency of landslide inducing storm events and recovery rate of the soil property between events. Despite such fluctuations, there are gradual declines of 7·5% in average total carbon content of topsoil and 9·5% in average soil depth to bedrock, since the time of forest clearance. Results have application to large‐scale sediment budget and water quality models and to the New Zealand Soil Carbon Monitoring System (CMS). Copyright © 2012 John Wiley & Sons, Ltd.